Penelitian Artificial Intelligence untuk Satelit Komunikasi menggunakan Jaringan Syaraf Tiruan (JST) - Jonathan Sinaga, Tommy (Fakultas Teknologi Informasi, 2024)
Satellite Communications offers the promise of periodic continuous service in uncovered and covered areas, with service scalability. However, several issues must be addressed first to realize these benefits, such as resource management, network control, network security, spectrum management, and satellite energy usage are more difficult compared to terrestrial networks. Meanwhile, artificial intelligence (AI), which includes deep machine learning, and security learning continues to grow as a research field and has shown a wide range of results in various applications, including wireless communications. In particular, the application of AI to various aspects of satellite communications is showing excellent potential, including beam- hopping, anti-jamming, network traffic forecasting, channel modeling, telemetry mining, ionospheric scintillation detection, interference management, remote sensing, behavioral modeling, space-air-ground integration, and energy management. This work provides an overview of AI and its diverse sub-fields, and modern algorithms. Some of the problems encountered in various aspects of satellite communication systems are discussed, and proposed and potential AI-based solutions are presented. Finally, an outlook on the field is described, with future steps expected.